The use of fixed time artificial insemination programmes for the use of sexed semen in block calving dairy heifers. (2nd May 2021) - Kerby, Mike; Clarke, Tom; Angel, Tom; Mackenzie, Kythé
Abstract : In seasonal block calving herds reproductive efficiency can have a significant impact on productivity and profitability. Within this it is key that the nulliparous heifers calve down promptly in the block, and if these heifers can have heifer calves it will expediate genetic gain. There is extensive research into the conception rates of differing protocols and the literature is reviewed to support the choice of protocol used in the subsequent case study. The case study uses a 6-day progesterone protocol with two injections of prostaglandin F2α and sexed semen; it demonstrated acceptable conception rates as well as the variability that can occur between different bulls' semen straws. Finally, the case study assesses the costs and benefits of the synchronisation programme and concludes a cost benefit of £88.55 per heifer.